Digital stories combined with POWER strategy supported by Canva in writing skill and social emotional learning - Jayanti, Made Dwi Surya Darmi; Kusuma, I Putu Indra; Marsakawati, Ni Putu Era (Indonesian Journal of Educational Development (IJED), 2025)
This study aimed to investigate whether the integration of digital stories and the POWER (Plan, Organize, Write, Edit, and Revision) strategy, supported by Canva, had a significant effect on students’ writing skill and social emotional development. The study was conducted at SMA Negeri 1 Tejakula, focusing on second grade students during the 2024/2025 academic year. It employed an experimental study with posttest only control group design. The total population consisted of 264 students from 8 classess. A sample of 132 students from four classes was selected using the intact group sampling technique and divided into experimental and control groups. The obtained data of the study were collected using two types of instruments: the writing test and questionnaire. The data were analyzed by using descriptive statistic and inferential statistic analysis, i.e one-way manova. The results revealed that: 1) student taught using digital stories combined with the POWER strategy and supported by Canva demonstrated significantly better writing skills compared to those taught using conventional methods; 2) students' social-emotional development also improved significantly under the same treatment.  The development of this new method needs to involve various field, not only principals and teachers, but also students and other researcher who are interested to know the effect of it in writing skill and social emotional of students in other subject.